Estudo da influência da fase sigma na fragilização do aço inoxidável superaustenítico ASTM A744 Gr. CN3MN: microdureza e resistência à corrosão localizada - Silva, Maria do Socorro da (2016)
Super austenitic stainless steels are mainly characterized by their high resistance to corrosion in different environments. The work environment temperature may favor the formation of phases that may affect the mechanical and corrosion-resistance properties of these steels. As a result of the amount of Mo, Ni and Cr, the precipitation occurs in secondary phases, being more common the phases sigma () and qui (). In order to evaluate the pit corrosion resistance as a result of σ phase quantification in the super austenitic studied, the following solubilization treatments were conducted: 1170 ºC for 2h and 1200 ºC for 4h and 8h (for formation of different volumetric fractions of the σ phase). Characterizations by means of optical and electron microscopy techniques were carried out before and after the cyclic polarization, as well as the use of the electron backscatter diffraction (EBSD), in addition to the open circuit potential (OCP) monitoring, verification of critical pit temperature (CPT) and measures of Vickers microhardness of phase precipitation in evaluate the effect mechanical properties. The results obtained were compared to the material as-received state (gross fusion), which was to subject to similarly analyzed. The presence of phase σ was verified in all conditions, with difference as regards the volumetric fraction as a result of the treatment applied. It may be then perceived that the solution annealing temperature increase promotes the volumetric fraction sigma phase increase, resulting in the material resistance reduction and Vickers microhardness increase. After the cyclic polarization unverified pit corrosion in any sample. For the sample with received the verification of critical pit temperature was 55 ° C, could not be verified pit corrosion other conditions. With the increase in the volume fraction of sigma phase it was possible to check the increase in hardness in the solubilized sample at 1200 ° C for 4 hours.